2020
DOI: 10.1007/s11906-020-01091-9
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome, Inflammation, and Salt-Sensitive Hypertension

Abstract: Purpose of Review Salt sensitivity of blood pressure (SSBP) is an independent predictor of death due to cardiovascular events and affects nearly 50% of the hypertensive and 25% of the normotensive population. Strong evidence indicates that reducing sodium (Na+) intake decreases blood pressure (BP) and cardiovascular events. The precise mechanisms of how dietary Na+ contributes to elevation and cardiovascular disease remain unclear. The goal of this review is to discuss mechanisms of salt-induced cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…As mentioned earlier in this chapter, excessive salt in the intestine is assumed to be trigger of onset of hypertension via dysbiosis of the gut microbiome (GM) [52]. In an animal study, it was reported that a decrease in lactobacillus murinus caused by salt intake altered the intestinal microbiome and contributed to the development of hypertension [53].…”
Section: Salt In Gut Mediating Through Microbiome and Gut-raas Cause Hypertensionmentioning
confidence: 97%
“…As mentioned earlier in this chapter, excessive salt in the intestine is assumed to be trigger of onset of hypertension via dysbiosis of the gut microbiome (GM) [52]. In an animal study, it was reported that a decrease in lactobacillus murinus caused by salt intake altered the intestinal microbiome and contributed to the development of hypertension [53].…”
Section: Salt In Gut Mediating Through Microbiome and Gut-raas Cause Hypertensionmentioning
confidence: 97%
“…A different but related issue is the effect of excess dietary salt consumption on the intestinal microbiota, which has been recognized as an integral part of our immune system [42]. It was reported that a salt load in healthy volunteers reduced the abundance of various Lactobacillus species in faecal samples, and this was associated with a rise in the concentration of proinflammatory TH17 cells in the blood [43].…”
Section: Sodiummentioning
confidence: 99%
“…AH is a potent modifiable cardiovascular (CV) risk factor and is the leading cause of mortality related to chronic kidney failure, ischemic heart disease and stroke [ 3 , 4 , 5 , 6 ]. According to ATP III criteria, MetS is characterized by at least three of the following five parameters: glycemia >100 mg/dL or glucose-lowering therapy, high-density lipoprotein- cholesterol (HDL-C) <40 mg/dL (men) or HDL-C <50 mg/dL (women) or lipid-lowering therapy, triglycerides (TG) >150 mg/dL, waist circumference (WC) >102 cm (men) or >88 cm (women), BP > 130/85 mmHg or anti-hypertensive therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…High salt intake is a well-known risk factor for AH and CV diseases [ 17 , 32 ]. At gut level, sodium interacts with commensal microbiota and can lead to AH, as recently explored by several authors [ 4 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%